Secondary school-based Restorative Interventions – What are the perceptions and experiences of the young people who are identified as ‘wrong-doers’? - Cooper-Johal, Jusleen (2016)
The historical origins of Restorative Practices (RPs) can be traced back to the Māori communities in New Zealand (Wearmouth & Berryman, 2012). In the 1980s and 1990s RPs were applied in the criminal justice sector and a decade later in the educational sector (McCluskey, Lloyd, Stead, Kane, Riddell & Weedon, 2008b). According to a large-scale survey of English schools in 2009, some 69% reported to sometimes employ RPs (Kane, Lloyd, McCluskey, Maguire, Riddell, Stead & Weedon, 2009). The benefits of using RPs in schools are that it allows the focus to be shifted from punitive approaches to providing children with learning opportunities when conflict has occurred (Hopkins, 2003).